On Two-Dimensional Rangefinding Using a ∼1 nJ/∼100 ps Laser Diode Transmitter and a CMOS SPAD Matrix - Lauri W. Hallman; Sahba Jahromi; Jussi-Pekka Jansson; Juha Kostamovaara (IEEE Photonics Journal, 2018)
A potentially compact 2-D range profiler for noncooperative targets with a distance range of >10 m is demonstrated. A laser diode utilizing enhanced gain switching is used as a transmitter to provide short, high-energy optical pulses (∼1 nJ/140 ps). Cylindrical lenses spread the laser beam in one dimension and collimate the beam in the other dimension to illuminate a line shaped field of view of about 45°. A similarly shaped field of view for the detector is realized with a single-photon avalanche diode (SPAD) detector matrix. Compared with a flash 3-D rangefinder, the 2-D rangefinding scheme relaxes the SPAD and time-to-digital converter design requirements, increases the signal irradiance at the detector, can have better tolerance for background illumination, and it can be sufficient or advantageous in some applications. The distance measurement precision to each direction is inherently within a few centimeters (FWHM) since the laser pulse width and SPAD detector jitter both correspond with an optical pulse back-and-forth flight time of about a centimeter. Demonstration measurements show >15 Hz line rate and a lateral resolution of about 5 mrad to noncooperative targets at distances of more than 10 m.